2005
DOI: 10.1182/blood-2004-05-2010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fondaparinux on platelet activation in the presence of heparin-dependent antibodies: a blinded comparative multicenter study with unfractionated heparin

Abstract: Heparin-induced thrombocytopenia (HIT)is a complication of heparin therapy caused by antibodies against a complex of platelet factor 4 and heparin. Fondaparinux (Arixtra) is a new synthetic selective factor Xa inhibitor. We performed a serologic study to determine the crossreactivity of HIT sera with fondaparinux. Using a prospective, blinded study design, 39 clinically and serologically confirmed sera from patients with HIT and 15 control sera were sent to 3 different laboratories, each of which specialized i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
121
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(127 citation statements)
references
References 33 publications
4
121
0
1
Order By: Relevance
“…In vitro studies demonstrated that in most of the cases fondaparinux did not activate platelets in the presence of anti-PF4/heparin antibodies [10]. Fondaparinux was also shown to reduce the risk of developing HIT in patients with baseline platelet-activating heparin-dependent antibodies [11].…”
Section: Solving Clinical Problems In Blood Diseasesmentioning
confidence: 99%
“…In vitro studies demonstrated that in most of the cases fondaparinux did not activate platelets in the presence of anti-PF4/heparin antibodies [10]. Fondaparinux was also shown to reduce the risk of developing HIT in patients with baseline platelet-activating heparin-dependent antibodies [11].…”
Section: Solving Clinical Problems In Blood Diseasesmentioning
confidence: 99%
“…Estudos recentes relatam que o fondaparinux apresenta eficiência e risco hemorrágico similares aos observados com HBPM, com a vantagem de apresentar menor risco de trombocitopenia induzida pela heparina (TIH) [16,21,26,27,28].…”
Section: Fondaparinux E Idraparinuxunclassified
“…Fondaparinux, which does not require APTT monitoring, has been successfully used for treatment of HIT as well as thrombosis prophylaxis in patients with a history of heparin sensitivity [6][7][8]. A recent prospective blinded study has demonstrated that fondaparinux does not react to sera of patients with HIT, further supporting its potential use in this setting [9]. Currently, there are no published reports of fondaparinux use as thrombosis treatment or as prophylaxis in APS, although its potential use in pregnancy has been evaluated in a mouse model.…”
Section: S G H O L T a N * S K K N O X And A T E F F E R Imentioning
confidence: 99%
“…Due to the rarity of the disorder, the available data on the incidence of bleeding episodes, prevalent clinical manifestations and treatment modalities are scarce [2][3][4][5][6][7]. Afibrinogenemia is sometimes associated with symptoms that are unusual in patients with defects of coagulation factors, such as thrombotic complications and miscarriages [8][9][10][11][12]. However, knowledge on the incidence and significance of these unusual symptoms is influenced by publication bias.…”
Section: S G H O L T a N * S K K N O X And A T E F F E R Imentioning
confidence: 99%